Pentingnya Peran Ayah dalam Mendidik Anak pada Aspek Perkembangan Sosial Emosional - Kireyna Shelomita; Desvi Wahyuni (CV. Ulil Albab Corp, 2023)
This article explains the importance of the father's role in the upbringing of children, especially in the socio-emotional developmental aspects. The role of the father in the life of the child is not only limited as a material provider, but also has a significant impact on the formation of the social and emotional well-being of a child. In essence, this article uses a literature study method for the framework of the penetration. Based on the analysis of previous research data obtained that the importance of the father's role in raising children is still very small. Only 21% of fathers help mothers raise their children. Furthermore, research (Wall & Arnold, 2007) shows that the father's role is often overlooked and the media over-exaggerates the role of mothers in raising children. Although the father had time for his children, some media articles questioning the father's involvement in childcare and child education explained that the father did not have time to participate in child care because his role was to nurture the family. The findings of research on the importance of the father's role in the upbringing of children show that the role of a father in raising a child is very important especially in terms of social and emotional development. Father not only plays the role of head of the family, but also has a major influence on the development of the child's personality.